High Levels of Physical Activity in Later Life Are Associated With Enhanced Markers of Mitochondrial Metabolism. (14th January 2020) - Joanisse, Sophie; Ashcroft, Stephen; Wilkinson, Daniel J; Pollock, Ross D; O'Brien, Katie A; Phillips, Bethan E; Smith, Ken; Lazarus, Norman R; Harridge, Stephen D R; Atherton, Philip J; Philp, Andrew
Abstract: The age-associated reduction in muscle mass is well characterized; however, less is known regarding the mechanisms responsible for the decline in oxidative capacity also observed with advancing age. The purpose of the current study was therefore to compare mitochondrial gene expression and protein content between young and old recreationally active, and older highly active individuals. Muscle biopsies were obtained from the vastus lateralis of young males (YG: 22 ± 3 years) and older (OG: 67 ± 2 years) males not previously engaged in formal exercise and older male master cyclists (OT: 65 ± 5 years) who had undertaken cycling exercise for 32 ± 17 years. Comparison of gene expression between YG, OG, and OT groups revealed greater expression of mitochondrial-related genes, namely, electron transport chain (ETC) complexes II, III, and IV ( p < .05) in OT compared with YG and OG. Gene expression of mitofusion (MFN)-1/2, mitochondrial fusion genes, was greater in OT compared with OG ( p < .05). Similarly, protein content of ETC complexes I, II, and IV was significantly greater in OT compared with both YG and OG ( p < .001). Protein content of peroxisome proliferator-activated receptor gamma, coactivator 1 α (PGC-1α), was greater in OT compared with YG and OG ( p < .001). Our results suggest that the aging process per se is not associated with a decline in gene expression and protein content of ETC complexes. Mitochondrial-related gene expression and protein content are substantially greater in OT, suggesting that exercise-mediated increases in mitochondrial content can be maintained into later life.